2009
DOI: 10.1177/0278364908096237
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Bounded-error State Estimation for Vehicle Tracking

Abstract: Estimating the configuration of a vehicle is crucial for its navigation. Most approaches are based on (extended) Kalman filtering or particle filtering. An attractive alternative is considered here, which relies on interval analysis. Contrary to classical extended Kalman filtering it allows global localization, and contrary to particle filtering it provides guaranteed results in the sense that a set is computed that contains all of the configurations that are consistent with the data and hypotheses. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…EKF use a probabilistic motion model to fuse sensor data [30]. We make an extension of this model to obtain an interval based model defined by Seignez et al [18]:…”
Section: Motion Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…EKF use a probabilistic motion model to fuse sensor data [30]. We make an extension of this model to obtain an interval based model defined by Seignez et al [18]:…”
Section: Motion Modelmentioning
confidence: 99%
“…Followed-up researchers focused on real-time implementation of such localization technique. Kieffer [17] and Seignez [18] presented results for a mobile robot navigating in an indoor environment, with odometers mounted on each rear wheel to measure the motion and sonars located in different directions to perceive the environment. The ability of interval method to cope with erroneous data and to obtain accurate estimations of the robot pose was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…x k−1|k−1 represents the state vector at time k-1, x k|k−1 represented the state vector after the prediction step, x k|k represents the state vector after the estimation step. The classical evolution model, described in [18], is considered:…”
Section: Predictionmentioning
confidence: 99%
“…An alternative to PF could be the bounded-error state estimation. Experiments have demonstrated that the approach is operational on vehicle navigating in an indoor environment or in an outdoor environment [11]. In this approach, known as set-membership or set-theoretic estimation, all model and measurement errors are assumed to be bounded, with known bounds.…”
Section: Introductionmentioning
confidence: 99%